ANALISIS KINERJA KEUANGAN KOPERASI BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS - J VONNY LITAMAHUPUTTY (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
This study aims to determine the financial performance of the Gita Bahari multi-business cooperative during the period 2017 to 2019. This type of research is descriptive research with quantitative approach.Data collection using interviews and documentation. The data analysis techniques in this study are ratio analysis based on financial performance which includes liquidity ratio (current ratio, quick ratio and cash ratio), solvency ratio (total asset to debt ratio and total equity to debt ratio) and profitability ratio (return on investment and return on equity). The results showed that the financial performance of the Gita Bahari multi-business cooperative based on liquidity and solvency ratios was in the unhealthy category. While the profitability ratio of cooperatives is in the healthy categor